Living Law on The Margins: A Critical Review of Article 2 of The 2023 Indonesian Penal Code - Antoni Putra; Lucky Raspati; Taufik Rachman; Iwan Kurniawan (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2026)
The recognition of living law in society, as stipulated in Article 2 of Law Number 1 of 2023 on the Indonesian Penal Code (KUHP), appears to be a progressive step toward respecting legal pluralism in Indonesia. However, this recognition is conditional and places customary law in a subordinate position to state law. This article critically examines how Article 2 of the KUHP systematically narrows the space for customary law and disregards the sociological reality of living legal traditions. This study employs a normative juridical research method, focusing on the analysis of statutory provisions, legal doctrines, and relevant academic literature. Customary law, which has long been effective in resolving social conflicts, is marginalized due to its perceived incompatibility with formalistic and universal legal principles. This article proposes a deliberative approach as an alternative through equal and dialogical engagement between state and customary legal systems, emphasizing affirmative recognition that respects the autonomy of local legal communities. In doing so, recognizing customary law should not be a limiting instrument but a means to strengthen contextual justice within Indonesia’s diverse society.